2019
DOI: 10.1002/cta.2617
|View full text |Cite
|
Sign up to set email alerts
|

A new six‐dimensional hyperchaotic system and its secure communication circuit implementation

Abstract: In the paper, a novel six-dimensional hyperchaotic system is proposed for secure communication. A detailed analysis of some relevant features, such as equilibrium stability, dissipation, bifurcation, and Lyapunov exponents. The resultsshow that there are hyperchaos, chaos, quasi-periodic, and periodic dynamic behaviors for our constructed hyperchaotic system. Then the six-dimensional hyperchaotic system is simulated and implemented, which verified its physical realizability. The six-dimensional hyperchaotic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The work on applications of chaotic synchronization in secure communication has grown dramatically in recent years [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Developing control systems for synchronization of various chaotic systems has been one of the main focuses of prior works, aiming to improve security in communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work on applications of chaotic synchronization in secure communication has grown dramatically in recent years [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Developing control systems for synchronization of various chaotic systems has been one of the main focuses of prior works, aiming to improve security in communication.…”
Section: Introductionmentioning
confidence: 99%
“…Jing Wang et al [ 35 ] conducted the implementation of analog hardware for a synchronization method; the chaotic system tested in this method is six-dimensional. In order to implement the hardware, all conditions are considered so that the theory of the proposed scheme is consistent with the simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…Chaotic and hyperchaotic systems have been used in most diverse contexts, including nonlinear identification [27]- [29], observation and control [30], [31], economy [32], [33], welding [34], [35], and secure communication [11], [21], [36], [37], [39]- [42]. In particular, chaos-based cryptography is a very active research topic in the literature, which is motivated by the pseudo-random behavior observed in chaotic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Chang [28] gave an idea of stability, chaos detection, and quenching chaos for the swing equation system. Wang et al [29] developed the six-dimensional hyperchaotic system and applied for secure communication circuit implementation. Wolf et al [30] introduced the main calculations that permit the assessment of nonnegative Lyapunov types from an exploratory time arrangement.…”
Section: Introductionmentioning
confidence: 99%